A Burkitt's Lymphoma Case Mimicking Crohn's Disease: A Case Report - Gulbanu Erkan; Mehmet Çoban; Aysun Çalıskan; Gokçe Kaan Ataç; Kamil Gulpınar; Bulent Degertekin; Atilla Korkmaz (Case Reports in Medicine)
Lymphomas are solid tumors that arise from lymphoid tissue and present themselves as Hodgkin's or non-Hodgkin's lymphoma. Particularly gastrointestinal lymphomas can be clinically confused with other gastrointestinal tumors as well as with diffuse and inflammatory bowel disease. Early diagnosis and treatment bear vital importance in the management of lymphomas due to their high proliferation rates. In this report, we are presenting a case which initially displayed clinical and radiological signs of Crohn's disease, but was eventually diagnosed as Burkitt's lymphoma by laparotomy, and also we aim to underscore the importance of differential diagnosis.